The role of early invasive, selective invasive, or conservative strategies in acute coronary syndromes - Vorster, Jean; Manga, Pravin (SA Heart Journal, 2017)
Acute Coronary Syndrome (ACS) comprises three related disorders. In ST-elevation myocardial infarction (STEMI) rapid restoration of flow in the infarct-related artery (via pharmacological or mechanical means) is of paramount importance to minimize necrosis. In patients presenting with Unstable Angina / Non-ST-segment myocardial infarction (UA/NSTEMI) the correct choice of the initial treatment strategy (early invasive vs. selective invasive vs. conservative) is imperative in assuring optimal patient outcomes. Various risk prediction models can assist in the decision making process in an individual patient. The timing of angiography and revascularization in patients selected for the early invasive strategy are important factors in determining the long-term outcome in this patient population subset.